2021
DOI: 10.1186/s12884-021-03733-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perinatal depression on risk of adverse infant health outcomes in mother-infant dyads in Gondar town: a causal analysis

Abstract: Background Approximately one-third of pregnant and postnatal women in Ethiopia experience depression posing a substantial health burden for these women and their families. Although associations between postnatal depression and worse infant health have been observed, there have been no studies to date assessing the causal effects of perinatal depression on infant health in Ethiopia. We applied longitudinal data and recently developed causal inference methods that reduce the risk of bias to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…The lack of associations between higher maternal depressive symptoms with infant nutritional status is consistent with previous studies where maternal common mental problems were not associated with nutritional status of under five years children in Ethiopia (14,28,29), but contrasts with several other studies from LMICs (16)(17)(18)(19)(30)(31)(32)(33)(34)(35) including findings from Ethiopia (36,37). Our finding is consistent with findings of high income settings (European cohort study (38) and the generation R study (39)) and upper middle income countries (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The lack of associations between higher maternal depressive symptoms with infant nutritional status is consistent with previous studies where maternal common mental problems were not associated with nutritional status of under five years children in Ethiopia (14,28,29), but contrasts with several other studies from LMICs (16)(17)(18)(19)(30)(31)(32)(33)(34)(35) including findings from Ethiopia (36,37). Our finding is consistent with findings of high income settings (European cohort study (38) and the generation R study (39)) and upper middle income countries (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Perinatal depression can have damaging effect on the wellbeing of the newborn, and that maternal emotional distress can even affect the fetus and impair the cognitive and behavioral development. Perinatal depression is attributed to inadequate prenatal care which can lead to poor nutritional health for the mothers and the infants, and a higher risk of infections in children (13,15,16). In some cases, it can also lead to negative maternal-infant interaction, behavioral problems in children, and in severe cases suicide and infanticide have also been reported (17).…”
Section: Impact Of Perinatal Depressionmentioning
confidence: 99%
“…In 2020, a systematic review in mainland China, which examined the prevalence of PND and its determinants, reported a 16.3%, 19.7%, and 14.8% pooled prevalence of PND, antenatal depression, and PPD, respectively [ 3 ]. PND entails various adverse health outcomes for both mothers and babies [ 1 , 4 , 5 ]. These include increased risk of preeclampsia, pregnancy, labor complications, infanticide or suicide for mothers and preterm births, low birth weight, and poor cognitive and emotional development for infants and newborns [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…PND entails various adverse health outcomes for both mothers and babies [ 1 , 4 , 5 ]. These include increased risk of preeclampsia, pregnancy, labor complications, infanticide or suicide for mothers and preterm births, low birth weight, and poor cognitive and emotional development for infants and newborns [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%